Indigenous languages, cultural cognition and public interest in post-apartheid South Africa - Motsogi, Mphonyana (University of the Witwatersrand, Johannesburg, 2024)
The South African Language Policy Act was enacted in response to the apartheid system, which systematically marginalised indigenous languages and reduced them to non- official communication tools. The SABC (South African Broadcasting Corporation) and ICASA (Independent Communications Authority of South Africa) have the responsibility of ensuring that all official languages of South Africa, including minority indigenous languages, are equally represented in the broadcasting space. This study examines the extent to which the SABC effectively enforces language quota systems, as mandated by ICASA, to promote and safeguard the development of the Sotho/Tswana language category and other official indigenous languages in the broadcasting space; for instance, Tshivenda. The multilingual program, Motswako is used as a (A case study); the programme was broadcast on SABC 2. The study analysed the South African broadcasting model in conjunction with ICASA's language policy regulation document. The study employed language planning theories and the communication accommodation theory to gain insight into the language context and multilingualism in South Africa. In addition, the study focused on the examination of public interest with the objective to investigate the involvement of the public in policy planning and development. The significance of media practitioners as representatives of the public was understood through the application of the social responsibility theory. This research project employed both qualitative and quantitative research methods, specifically analysing language policy documents from both the SABC and ICASA and other relevant articles on language planning and policy. The quantitative route was taken to quantify within episodes; the number of time hosts code switch/mix to western languages. The data collection process involved the collection of policy documents and articles, and the findings were analysed through thematic analysis. A total of eighteen episodes from the multilingual programme Motswako were selected and evaluated according to the language editorial policy principles of the SABC and the language quota systems established by ICASA. The study revealed that both the SABC and ICASA lack effective mechanisms to monitor and safeguard the development of indigenous languages in locally produced programs.
A research report submitted in fulfillment of the requirements for the Master of Arts (African languages and linguistics), In the Faculty of Humanities,School of Literature, Language and Media, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Indiginous languages" "Sotho-tswana language category" "ICASA" "SABC" "Media" "Post apartheid"; SDG-4: Quality education